Desarrollo De Un Sub-Módulo De Historia Clínica Laboral Dentro Del Erp Para La Empresa Srf Consultores (2021)
In the company SRF consultants, the management of the workers' medical history is done manually. The aim is to automate this process by creating a Clinical History module that allows the management of all the information of the workers regarding their medical history, this module would be integrated with the company's ERP. It would impact the response time in the consultation of the medical history and all the management that is given to it, because the process would be automated. This is the option that is chosen to solve the problem that the project has because the company has Microsoft Dynamics in all processes and in this way the costs associated with hiring external software would be reduced. For the progression of the project, the Scrumban methodology was used, and with the methodology it was possible to automate the management of the occupational medical history